2000
DOI: 10.3168/jds.s0022-0302(00)75181-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dietary Protein Level and Origin on the Flow of Mucin Along the Small Intestine of the Preruminant Calf

Abstract: The objective of this study was to investigate the effect of the dietary crude protein (CP) content and origin on the flow of mucin protein along the small intestine of the preruminant calf. Diets contained 1, 10, 20 and 28% of CP supplied by skim milk powder (SMP) in experiment 1. Diets differed by the nature of protein [soybean protein concentrate (SPC), partially hydrolyzed soybean protein isolate (HSPI) or potato protein concentrate (PPC)] in experiment 2. Duodenal, jejunal, and ileal digesta were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 21 publications
5
43
2
Order By: Relevance
“…Using a specific enzyme-linked immunosorbent assay (ELISA), investigators in our laboratory measured the flow of mucin along the small intestine of preruminant calves that were fed a protein-free diet. 13,14 The basal flow of mucin protein at the duodenum, jejunum, and ileum was 1.1, 1.8, and 4.0 g/kg DMI, respectively (i.e., 2.1, 3.4, and 7.5 g mucin/kg DMI). The latter value at the ileum was twice the value obtained in pigs (3.9 g/kg DMI).…”
Section: Roles In Relation With Gut Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a specific enzyme-linked immunosorbent assay (ELISA), investigators in our laboratory measured the flow of mucin along the small intestine of preruminant calves that were fed a protein-free diet. 13,14 The basal flow of mucin protein at the duodenum, jejunum, and ileum was 1.1, 1.8, and 4.0 g/kg DMI, respectively (i.e., 2.1, 3.4, and 7.5 g mucin/kg DMI). The latter value at the ileum was twice the value obtained in pigs (3.9 g/kg DMI).…”
Section: Roles In Relation With Gut Healthmentioning
confidence: 99%
“…1 Nevertheless, in these calves, the contribution of mucin amino acids to the total flow of amino acids was quite high for lysine (40%), and to a lesser extent for glutamic acid (29%), and threonine, serine, and aspartic acid (25% each). 14 We also measured the flow of mucin protein at the duodenum, which originate from the upper GIT and the stomach. This would represent 25% of the ileal loss of mucin protein, 14 which concurs with the value in pigs provided by Lien et al 11…”
Section: Roles In Relation With Gut Healthmentioning
confidence: 99%
“…Phytate was probably present in both soya preparations (57) and may have triggered these increases in alkaline phosphatase activity. Therefore, it is noteworthy that Montagne et al (61) found that both soya preparations substantially increased the flow of mucin protein in the duodenum, jejunum and ileum in pre-ruminant calves by approximately 70 -90%. Moreover, Montagne et al (62) determined the effect of these partial substitutions on the apparent digestibility of cystine, lysine and threonine at the jejunal and ileal levels.…”
Section: Ternary Protein -Phytate Complexesmentioning
confidence: 99%
“…11,12 The control diet was based on skim milk powder. The other three diets contained a mixture of skim milk powder and plant products.…”
Section: Materials and Methods Dietsmentioning
confidence: 99%